Once‐a‐week or every‐other‐day urethra‐sparing prostate cancer stereotactic body radiotherapy, a randomized phase II trial: 18 months follow‐up results. (11th March 2020) - Zilli, Thomas; Jorcano, Sandra; Bral, Samuel; Rubio, Carmen; Bruynzeel, Anna M.E.; Oliveira, Angelo; Abacioglu, Ufuk; Minn, Heikki; Symon, Zvi; Miralbell, Raymond
Abstract: Background: To present the 18 months results from a prospective multicenter phase II randomized trial of short vs protracted urethra‐sparing stereotactic body radiotherapy (SBRT) for localized prostate cancer (PCa). Methods: Between 2012 and 2015, a total of 170 PCa patients were randomized to 36.25 Gy in 5 fractions (6.5 Gy × 5 to the urethra) delivered either every other day (EOD, arm A, n = 84) or once a week (QW, arm B, n = 86). Genitourinary (GU) and gastrointestinal (GI) toxicity (CTCAE v4.0 scale), IPSS, and QoL scores were assessed at baseline, at the 5th fraction (5fx), 12th weeks (12W), and every 6 months after SBRT. The primary endpoint was biochemical control at 18 months and grade ≥ 3 toxicity (including grade ≥ 2 for urinary obstruction/retention) during the first 3 months. Results: Among the 165 patients analyzed, the toxicity stopping rule was never activated during the acute phase. Maximum acute grade 2 GU toxicity rates at 5fx were 17% and 19% for arms A and B, respectively, with only 2 cases of grade 2 GI toxicity at 5fx in arm A. At month 18, grade ≥ 2 GU and GI toxicity decreased below 5% and 2% for both arms. No changes in EORTC QLQ‐PR25 scores for GU, GI, and sexual domains were observed in both arms between baseline and month 18. Four biochemical failures were observed, 2 in each arm, rejecting the null hypothesis of an unfavorable response rate ≤ 85% in favor of an acceptable ≥ 95% rate. Conclusions: At 18 months, urethra‐sparing SBRT showed a low toxicity profile, with minimal impact on QoL and favorable biochemical control rates, regardless of overall treatment time (EOD vs QW). Abstract : Dose per fraction and overall treatment time can impact tolerance of prostate SBRT. Urethra‐sparing SBRT showed a low toxicity profile and minimal impact on QoL. An EOD or QW SBRT schedule had a comparable tolerance and efficacy at 18 months.